Penerapan Free Ongkir System pada Pemasaran Seafood Melalui Facebook - Achmad Maimun Anwar (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Advances in technology also have an impact on business actors, especially traders. Cultural changes in marketing strategies must be carried out by utilizing digital. AB sea food as a business actor that provides marine products has also revolutionized its marketing strategy. This is done to maintain the continuity of its business so as not to lose competitiveness. This study aims to determine the application of the free shipping system in seafood marketing strategies through Facebook. This research uses descriptive qualitative method. Data obtained from three aspects, namely observation, interviews and documentation. The results obtained from this study indicate that the application of the free shipping system in the marketing strategy through Facebook is increasing the attractiveness of consumers in choosing AB sea food products, the more consumers and resellers asking to partner, so the result is an increase in income.